The role of immunohistochemical research at the diagnosis of neoplastic lesions of the cervix - A I Shchegolev; O D Mishnev (IP Berlin A.V., 2016)
The analysis of literature data about the use of immunohistochemical markers for the diagnosis and differential diagnosis of cervical lesions. The most significant assistance in identifying and determining the degree of cervical intraepithelial neoplasia has immunohistochemical detection of Ki-67 and p16. Shows the changes of p63, topoisomerase, C-erbB-2, cyclin D1 at the cervical intraepithelial neoplasia of different degrees of severity and cervical cancer. It is concluded that the immunohistochemical research is legitimate considered as an effective method for histopathological studies. It allows to carry out an objective diagnosis of neoplastic lesions of the cervix, to carry out their differential diagnosis with reactive and tumor-like changes, as well as to determine the prognosis of the disease.